2012
DOI: 10.1038/cr.2012.146
|View full text |Cite
|
Sign up to set email alerts
|

Cytokinin signaling regulates pavement cell morphogenesis in Arabidopsis

Abstract: The puzzle piece-shaped Arabidopsis leaf pavement cells (PCs) with interdigitated lobes and indents is a good model system to investigate the mechanisms that coordinate cell polarity and shape formation within a tissue. Auxin has been shown to coordinate the interdigitation by activating ROP GTPase-dependent signaling pathways. To identify additional components or mechanisms, we screened for mutants with abnormal PC morphogenesis and found that cytokinin signaling regulates the PC interdigitation pattern. Redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 46 publications
0
25
0
Order By: Relevance
“…The algorithms used to track and measure growth in these model systems cannot directly be applied to quantify PC characteristics, as they oversimplify PC shape geometry, and comparable quantification methods suitable for robust analysis of PCs are lacking. In most existing studies that analyzed PC characteristics, differences in PC shape between mutants and wild type were quantified by the analysis of single shape parameters only (Tisné et al, 2008;Xu et al, 2010;Li et al, 2013) or by a combination of a few select shape parameters (Fu et al, 2005;Guo et al, 2015). Although sufficient for direct comparison of phenotypes, the limited shape information reduces the informational value of the individual measurements and hampers a comprehensive comparison of phenotypes identified in different studies and from different laboratories (Ivakov and Persson, 2013;Wu et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The algorithms used to track and measure growth in these model systems cannot directly be applied to quantify PC characteristics, as they oversimplify PC shape geometry, and comparable quantification methods suitable for robust analysis of PCs are lacking. In most existing studies that analyzed PC characteristics, differences in PC shape between mutants and wild type were quantified by the analysis of single shape parameters only (Tisné et al, 2008;Xu et al, 2010;Li et al, 2013) or by a combination of a few select shape parameters (Fu et al, 2005;Guo et al, 2015). Although sufficient for direct comparison of phenotypes, the limited shape information reduces the informational value of the individual measurements and hampers a comprehensive comparison of phenotypes identified in different studies and from different laboratories (Ivakov and Persson, 2013;Wu et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…With improving imaging techniques, several studies addressed the dynamics and changes of PC shape during leaf development and expansion (Iwata and Ukai, 2002;Andriankaja et al, 2012;Elsner et al, 2012;Barbier de Reuille et al, 2015;Vanhaeren et al, 2015). Key regulators of PC interdigitation were identified by mutant phenotyping (Xu et al, 2010;Lin et al, 2012;Li et al, 2013;Guo et al, 2015). In many cases, PC characteristics were described by global descriptors, such as area or circularity, or by skeleton-based approaches (Horiguchi et al, 2006;Staff et al, 2012).…”
mentioning
confidence: 99%
“…Cell polarity and morphogenesis, which are critical for plant organ development, are modulated by numerous cytoskeleton-associated proteins and various developmental and environmental signals (Fu et al, 2005;Hamant et al, 2008;Kleine-Vehn et al, 2008;Xu et al, 2010;Li et al, 2013). Cell polarity is often presented as a polar distribution of molecules within the cell.…”
Section: Discussionmentioning
confidence: 99%
“…The interdigitated lobes and indentations of PCs result from intercalary growth (Fu et al, 2005). he cell polarity and morphogenesis are dependent on cell adhesion, signaling networks, the cytoskeleton, and protein transport (Falbel et al, 2003;Mathur et al, 2003;Fu et al, 2005;Wang et al, 2007;Chary et al, 2008;Xu et al, 2010;Li et al, 2013). A well-known mechanism that controls interdigitated growth of PCs is Rho of Plant (ROP) GTPase-mediated cytoskeletal reorganization in Arabidopsis (Fu et al, 2002(Fu et al, , 2005(Fu et al, , 2009).…”
mentioning
confidence: 99%
“…Ruzicka et al [38] suggested that cytokinin affected auxin transport in the root meristem via the modification of PIN protein expression. According to Li et al [39], auxin regulates spatial coordination of cell expansion in leaf interacting with ABP1 and activating Rho GTPases, while cytokinin inhibits ROP2 activity which regulates PIN1 distribution and suppresses morphogenesis in leaf. In this connection, the data of Bosch and Franklin-Tong [40] about the acidification of pollen tube cytoplasm, which accompanied mechanism of self-incompatibility, arouse interest.…”
Section: Regulation Of Petunia Pollen Tube Growth By Phytohormonesmentioning
confidence: 99%